Assessment of DNA Damage and Telomerase Activity in Exfoliated Urinary Cells as Sensitive and Noninvasive Biomarkers for Early Diagnosis of Bladder Cancer in Ex-Workers of a Rubber Tyres Industry. (30th April 2014) - Cavallo, Delia; Casadio, Valentina; Bravaccini, Sara; Iavicoli, Sergio; Pira, Enrico; Romano, Canzio; Fresegna, Anna Maria; Maiello, Raffaele; Ciervo, Aureliano; Buresti, Giuliana; Zoli, Wainer; Calistri, Daniele
Abstract : The aim of the present study was to identify sensitive and noninvasive biomarkers of early carcinogenic effect at target organ to use in biomonitoring studies of workers at risk for previous occupational exposure to potential carcinogens. Standard urine cytology (Papanicolaou staining test), comet assay, and quantitative telomerase repeat amplification protocol (TRAP) assay were performed in 159 ex-rubber workers employed in tyres production and 97 unexposed subjects. In TRAP positive cases, a second level analysis using FISH (Urovysion) was done. Cystoscopy results were available for 11 individuals whose 6 FISH/TRAP/comet positive showed in 3 cases a dysplastic condition confirmed by biopsy, 1 comet positive resulted in infiltrating UBC to the biopsy and with hyperplasia and slight dysplasia to the urinary cytology, 1 comet positive resulted in papillary superficial UBC to the biopsy, 1 FISH/TRAP positive showed a normal condition, and 2 TRAP positive showed in one case a phlogosis condition. The results evidenced good concordance of TRAP, comet, and FISH assays as early biomarkers of procarcinogenic effect confirmed by the dysplastic condition and UBC found by cystoscopy-biopsy analysis. The analysis of these markers in urine cells could be potentially more accurate than conventional cytology in monitoring workers exposed to mixture of bladder potential carcinogens.